Efektivitas Pembelajaran Vee Diagram dalam Meminimalisir Kesalahan pada Perancangan Eksperimen - Handayani Handayani (Universitas Wiralodra, 2020)
Designing experiments is activity-based laboratory learning where laboratory activities lead to scientific ideas which emphasizes qualitative processes that aim to encourage conceptual changing toward the students. Experimental designs made by students are still found many mistakes. These in designing experiments could be minimized by applying vee diagrams. The application of Vee Diagrams helps students in designing experiments, therefor it can minimize the mistakes commonly done in designing experiments especiallyin practical learning. The research method was used is action research consisting of two cycles. The decrease of error in designing experiments is analyzed as a percentage at each research cycle. The data were sourced from third semester biology education students who taking biochemistry courses. Data obtained from the error analysis rubric in designing experiments, questionnaire responses of students in design experiments and vee diagrams rubric. The results showed that the application of vee diagrams can minimize errors in design experiments with the greatest decrease in errors at the stage of making hypotheses while the smallest decrease at the stage of analyzing data.